Hubungan Ilmu Jiwa Agama dengan Aktivitas Keagamaan dalam Kehidupan Bermasyarakat - Sudirman Sudirman (MODELING: Jurnal Program Studi PGMI, 2021)
In human life, religious entities and human psychological processes cannot be separated from each other, like interconnected chains. In the context of religious society, it is not uncommon for daily behavior to be determined more by the results of experience on religious beliefs, in the sense that behavior that occurs in human practical life is a manifestation of belief in God. The purpose of this study is to explain the relationship between religious psychology and religious activities in social life. This research uses qualitative research methods with descriptive analytic research. The result of this research is that the psychology of religion in humans consists of monistic theory and faculty theory. Monistic theory explains that the spiritual source of religion in humans comes from a single source, as the basis of their thinking. Meanwhile, the faculty theory reveals that the spiritual source of religion in humans is a combination of several psychological functions, namely; the function of creativity (reason), the function of taste (emotion), the function of intention (will) related to religious activities. This is evidence that religious psychology and religious activities have a parallel correlation.